(untitled) (International Journal of Food and Nutritional Sciences, 2020)
In the 21st century, advanced communication technology has affected every aspect of society so much that today’s society cannot even imagine a world without social media. Today, social media has established its dominance in every field. Especially in the field of Indian politics, it plays an important role in the active political participation of politicians. Independent media has an important role in the foundation of Indian democracy. The role of Indian media becomes more important when it plays an important role in influencing political outcomes during elections. However, in Indian politics, social media has developed on various platforms and in various forms. Social media platforms like Twitter, Facebook, Instagram, YouTube and WhatsApp provide new ways to encourage Indian voter participation in political life.